Values of trust in the 12th grade Islamic education textbook in Jordan - Alsalti, Mahmoud (International Journal of Innovative Research and Scientific Studies, 2025)
This paper explores the degree of inclusion of the values of trust in the content of the 12th-grade Islamic Education textbook in Jordan, given the importance of trust as a fundamental value in Islam and its role in building societies. A descriptive-analytical approach was utilized to analyze the textbook's content and categorize values related to trust according to their frequency and presentation, supplemented by a survey of the subject's teachers. The results indicated that values such as "belief in God" (4.81%), "piety" (4.55%), and "wealth preservation" (3.64%) are the most frequently mentioned. However, values such as "integrity" and "fulfilling one's rights" ranked last. Moreover, the findings revealed that the textbook focuses on doctrinal aspects while lacking contemporary practical examples of trust. This paper is of high significance as it calls for developing the Islamic education curriculum based on values, incorporating real-life examples and interactive activities, and organizing training courses for teachers to enhance methods of teaching Islamic values. Considering the results, the study recommends reinforcing the concepts of trust in Islamic education textbooks in a more comprehensive manner, with a focus on their practical applications in daily life and society, and diversifying the methods of presenting trust in textbooks by incorporating Quranic stories, Prophetic hadiths, and real-life examples that reinforce students' moral values.